PENGEMBANGAN SUMBER DAYA MANUSIA MADURA PASCA SURAMADU - Mohammad Kosim (Institut Agama Islam Negeri Madura)
Abstrac Suramadu bridge is like the dream comes true. Muderese must feel delighted since the problem of transportation is now resolved. On the other hand, the bridge arises a challenge, as Madura will be an open area with its consequences. Madurese people which have been marginalized by the nasional development agenda, seem are not ready to face a competing challenge. Therefore, the development of human resource of Madurese is urgently ruquired. Kata-kata kunci madura, suramadu bridge, education